1972
DOI: 10.1002/pssa.2210100104
|View full text |Cite
|
Sign up to set email alerts
|

The ordering of hydrogen in β-vanadium hydride

Abstract: Electron microscope specimens of vanadium, thinned by a technique known to add hydrogen, showed evidence for ordering in β‐vanadium hydride. Extra half‐order reflections were observed and concluded to be due to scattering from hydrogen. The transformation between the ordered and disordered phases occurs reversibly at a specific temperature in the range 160 to 190 °C depending on the specimen. The reciprocal lattice as determined by electron diffraction was shown to be in the monoclinic Laue group. Indirect evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 8 publications
(1 reference statement)
0
20
0
Order By: Relevance
“…BCT with c/a = 1.1 [17], but also reported to be monoclinic (a = 91°) [19] Occupancy in O Z1 octahedral sites [18,20] Exists in the range VH 0.41 -VH 0.61 below 175°C [21] e Called b 2 by Fukai [22] Equal [16] g Probably similar to b but with higher degree of order [16] counting statistics the NiTi 2 -rich alloy was examined independently. Fig.…”
Section: Nitimentioning
confidence: 99%
“…BCT with c/a = 1.1 [17], but also reported to be monoclinic (a = 91°) [19] Occupancy in O Z1 octahedral sites [18,20] Exists in the range VH 0.41 -VH 0.61 below 175°C [21] e Called b 2 by Fukai [22] Equal [16] g Probably similar to b but with higher degree of order [16] counting statistics the NiTi 2 -rich alloy was examined independently. Fig.…”
Section: Nitimentioning
confidence: 99%
“…Simultaneous studies (Somenkov, ]~ntin, Chervyakov, Wanagel, Sass & Batterman, 1972;Arons, Bohn & Lfitgemeier, 1972) including the present work demonstrate amply that the fl phase exists as monoclinic with the D atoms in octahedral sites. This same composition can have D largely in tetrahedral sites at elevated temperatures in the region.…”
Section: Structural Transitions In Vanadium Deuteridesmentioning
confidence: 88%
“…5, can be described as a b.c.c, lattice distorted to a b.c.t, with the e of the tetragonal cell in the horizontal direction. The D atoms are shown along alternate (T01) planes, as suggested by Wanagel, Sass & Batterman (1972), but octahedral sites have been chosen for the D's, rather than tetrahedral sites, for reasons that will become obvious below.…”
Section: The/3 Phasementioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of neutron, electron and X-ray diffraction experiments it had been reported that the crystal structure of a vanadium hydride ␤ 1 -V 2 H is body-centred monoclinic [1][2][3][4][5][6][7], or body-centred tetragonal [8,9], with an ordered arrangement of hydrogen atoms. This monoclinic structure is a pseudotetragonal one with an axial ratio of c 0 /a 0 ∼ 1.1 (c 0 and a 0 ; lattice parameters in the c-direction and the a-direction, respectively) and a slight inclination of the c 0 axis (α 0 ∼ 90.3 • ).…”
Section: Introductionmentioning
confidence: 99%